Detection of Similar Code Fragments Using Adjacency Structures - Kumar, Mukesh (My University, 2012)
Software clones are identical or similar pieces of code. They are often the result of copy–and–paste activities as ad-hoc code reuse by programmers. Software clones research is of high relevance for the industry. Many researchers have reported high rates of code cloning in both industrial and open-source systems. Code clone detection is the common aspect of reuse activity. Copying code fragments and then reuse with or without modifications are common activities in software development. This type of reuse approach of existing code is called code cloning and the pasted code fragment is called a clone of the original [1]. Existing approaches does not make use of adjacency structures and their properties. This thesis presented an efficient way of finding code clones by using adjacency structure. A directed graph of the source code is developed and information is parsed into adjacency structure. Using the properties of adjacency structure find in-degree and out-degree of a particular directed graph. Our insight is to deduce the flow on a particular node of the directed graphs to find the similarity between the nodes of the directed graph and then find the similar code fragments using similar code detection tools.
M.E. (Software Engineering)
Keywords: Similar Code Fragments; Adjacency Structures